Oral health related quality of life among special community adult population with low socioeconomic status residing in Guntur city, Andhra Pradesh: A cross-sectional study - N R Sirisha; P Srinivas; S Suresh; T Devaki; R Srinivas; B Vikram Simha (Wolters Kluwer Medknow Publications, 2014)
Introduction: Yenadis are one the major tribe of Andhra Pradesh. They are special community people with low socioeconomic status (SES) and they do jobs like collecting trash from garbage for their livelihood. Their life style, livelihood practices may have an impact on their oral health. Aim: The aim was to assess the impact of SES on oral health related quality of life in yenadi's community. Materials and Methods: A total of 156 adults residing in Yenadi colony in Guntur city were interviewed with oral health impact profile-14 questionnaire which was translated to local language, followed by clinical examination for dentition status and periodontal status. Data from subjects who were missed on the day of examination were collected on consecutive days. Demographic details, oral hygiene practices and personal habit details were collected. Results: Sufficient reliability (0.8) and validity were demonstrated for questionnaire. The associated factors effecting quality of life are gender (P = 0.02), age (0.005), SES (0.001), oral hygiene aid (0.001) and personal habits (P = 0.001). The mean decay missing filled total value of the study subjects was 3.69 ± 2.4. Among the study subjects, 52.7% of study subjects had calculus, and 25.6% of study subjects had pockets >6 mm or more. Conclusion: This study revealed high level of oral disease and poor perception of oral health among the people residing in that area, which is due to lack of knowledge of existing problems.